2008
DOI: 10.1021/es702693c
|View full text |Cite
|
Sign up to set email alerts
|

Development of Regenerable MgO-Based Sorbent Promoted with K2CO3 for CO2 Capture at Low Temperatures

Abstract: To improve their CO2 absorption capacity, alkali-based sorbents prepared by impregnation and wet mixing method of potassium carbonate on supports such as activated carbon and MgO (KACI30, KACP30, KMgI30, and KMgP30), were investigated in a fixed bed reactor (C02 absorption at 50-100 degrees C and regeneration at 150-400 degrees C). Total CO2 capture capacities of KMgI30-500 and KMgP30-500 were 178.6 and 197.6 mg CO2/g sorbent, respectively, in the presence of 11 vol % H2O even at 50 degrees C. The large amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
166
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(170 citation statements)
references
References 22 publications
4
166
0
Order By: Relevance
“…4(b) and 4(c). As listed in Table 3, compared to pure MgO, the MgO + K 2 CO 3 mixture only has about 10 K increase on its T 1 and T 2 values, which indicates that adding K 2 CO 3 (or K 2 O) does not increase the maximum CO 2 capture temperature much, but could affect its CO 2 capture capacity and kinetics as demonstrated experimentally in the literatures (Lee et al, 2006(Lee et al, , 2008Xiao et al, 2011). As we know that another potential advantage of mixing solids is to gain entropy and to increase the surface area of active part of the solid for having faster reaction rate.…”
Section: Application To Pre-and Post-combustion Co 2 Capture Technolomentioning
confidence: 77%
See 3 more Smart Citations
“…4(b) and 4(c). As listed in Table 3, compared to pure MgO, the MgO + K 2 CO 3 mixture only has about 10 K increase on its T 1 and T 2 values, which indicates that adding K 2 CO 3 (or K 2 O) does not increase the maximum CO 2 capture temperature much, but could affect its CO 2 capture capacity and kinetics as demonstrated experimentally in the literatures (Lee et al, 2006(Lee et al, , 2008Xiao et al, 2011). As we know that another potential advantage of mixing solids is to gain entropy and to increase the surface area of active part of the solid for having faster reaction rate.…”
Section: Application To Pre-and Post-combustion Co 2 Capture Technolomentioning
confidence: 77%
“…A similar double salt Cs 2 Mg(CO 3 ) 2 was also observed in the Cs promoted triglyceride transesterification over MgO nanocatalysts (Montero et al, 2010). The K 2 CO 3 -promoted MgO-based sorbent was investigated by several research groups (Lee et al, 2006;Lee et al, 2008;Xiao et al, 2011). Their results showed that its CO 2 capture capacity could be as high as 197.6 mg CO 2 /g, and after CO 2 absorption the double salts K 2 Mg(CO 3 ) 2 and K 2 Mg(CO 3 ) 2 ·4(H 2 O) were formed.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Solid sorbents based on alkali and alkali earth metals using Al 2 O 3 (Lee et al, 2011), activated carbon (Hirano et al, 1995;Hayashi et al, 1998;Lee and Kim, 2007), TiO 2 (Lee et al, 2006), MgO (Lee et al, 2008b), ZrO 2 (Lee et al, 2009(Lee et al, , 2013 and SiO 2 (Lee et al, 2006), etc. as supporters with various preparation methods have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%